2016
DOI: 10.1152/ajpheart.00696.2015
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial reverse remodeling: how far can we rewind?

Abstract: Heart failure (HF) is a systemic disease that can be divided into HF with reduced ejection fraction (HFrEF) and with preserved ejection fraction (HFpEF). HFpEF accounts for over 50% of all HF patients and is typically associated with high prevalence of several comorbidities, including hypertension, diabetes mellitus, pulmonary hypertension, obesity, and atrial fibrillation. Myocardial remodeling occurs both in HFrEF and HFpEF and it involves changes in cardiac structure, myocardial composition, and myocyte def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 281 publications
(232 reference statements)
1
23
0
3
Order By: Relevance
“…This may be explained by the fact that HFpEF and HFrEF have different patterns of myocardial remodelling arising from their different pathophysiological mechanisms . Some evidence points towards the stronger involvement of systemic inflammation associated with HFpEF, which may also impact the remodelling process …”
Section: Discussionmentioning
confidence: 99%
“…This may be explained by the fact that HFpEF and HFrEF have different patterns of myocardial remodelling arising from their different pathophysiological mechanisms . Some evidence points towards the stronger involvement of systemic inflammation associated with HFpEF, which may also impact the remodelling process …”
Section: Discussionmentioning
confidence: 99%
“…Experimental and human studies have suggested relationships between ST2 and myocardial stretch, fibrosis, adverse cardiac remodelling, inflammation, impaired haemodynamics, and vascular disease [23]. Indeed, in experimental studies ST2 appears to play a pivotal role in LV remodeling; this process comprises changes in cardiac structure, myocardial composition, myocyte deformation, and multiple biochemical and molecular alterations that impact heart function and reserve capacity [24]. The currently available data are insufficient to allow us to determine conclusively whether the value of ST2 as a marker of cardiac remodelling is different in patients with and without diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial hypertrophy may develop into heart failure, which is an independent risk factor of cardiovascular diseases (Lazzeroni et al , ). It is important to find more effective targets in the attempt to attenuate myocardial hypertrophy (Rodrigues et al , ).…”
Section: Introductionmentioning
confidence: 99%